Developing English Speaking Materials for Students of Culinary Study Program at Vocational School through Task-Based Learning - Fitri Erawati; Eddy Setia (LINGUISTIK TERAPAN, 2016)
The objectives of this study are: 1) to evaluate the existing English speaking materials used currently by the culinary students; 2) to find out the relevant English speaking materials; 3) to develop the English speaking materials through task-based learning. This study was conducted by applying the four phases of educational research and development Gall, Gall and Borg. The technique of collecting the data are questionnaire and documentation. The technique of analyzing the data is descriptive technique. The source of the data is culinary students and existing syllabus and speaking materials. The result is all the students (100%) agree that the objective of the existing speaking materials is less relevant with the objective of the culinary study program. The score for the existing syllabus is 0.9, it means generally most of the element in the existing syllabus are less relevant with the culinary study program. The result is in grade ninety (90), it means that generally the whole package of the speaking materials are good, relevant and feasible to be learning source. Therefore, it is suggested for the English teacher to use the speaking materials in this study for the culinary students at SMKN 2 Kutacane.   Keywords: English speaking materials, culinary study, vocational school